Kehormatan sebagai Motif: Narasi Yudisial dan Pertanggungjawaban Pidana dalam Kasus Pembunuhan Kehormatan Qandeel Baloch - Zul Khaidir Kadir (INDO PUBLISHING, 2026)
The murder of Qandeel Baloch is often discussed as a symbol of honor-based violence in Pakistan, yet limited attention has been given to how courts formulate and evaluate honor as motive within criminal proof. This article aims to examine how honor operates in judicial narrative, criminal liability, and evidentiary sufficiency in the Qandeel Baloch case. It adopts a normative-doctrinal legal method through textual analysis of the 2019 judgment of the Additional Sessions Judge, Multan, the 2022 appellate ruling of the Lahore High Court, relevant provisions of the Pakistan Penal Code, and the Criminal Law (Amendment) (Offences in the Name or Pretext of Honor) Act 2016. The study finds that honor did not function as an autonomous basis of criminal liability. At trial, honor helped the court characterize the killing as intentional and sufficiently serious to warrant punishment despite familial forgiveness. Its legal force, however, weakened once the confession and supporting evidentiary basis were challenged on appeal. The case demonstrates that a socially persuasive honor narrative must remain subject to evidentiary discipline, individualized culpability, and a clear distinction between social context and legal proof.